Intellectual capital and innovation for sustainable smart cities: The case of N-Tuple of Helices - Matos, F.; Valter Vairinhos; Susanne Durst; Renata Paola Dameri (Intellectual capital management as a driver of sustainability: Perspectives for organizations and society, 2019)
The purpose of this chapter is to explore and discuss, in the context of Smart Cities (SC), the relations between three concepts: Intellectual Capital (IC), Innovation Process (IP) and Sustainability (S). It is important to note that, in this context, the concept of IC refers to Smart Cities Intellectual Capital (SCIC), which is characterised by four components (Human Capital, Process Capital, Renewal Capital, Clients Capital), also used for Nations IC. The Innovation analysis considers two models: the first one expresses the dependencies and limits of innovation, resulting from physical limitations such as city area and city population; and the second one is the N-Tuple of Helices model. The concept of Smart City will be modelled as a living being capable of rational behaviour, knowledge production, and intellectual activity.